Pulmonary haemorrhage in neonates: Systematic review of management. (28th October 2021) - Barnes, Melissa E.; Feeney, Emily; Duncan, Andrew; Jassim, Samher; MacNamara, Honora; O'Hara, Joseph; Refila, Beshoy; Allen, John; McCollum, Danielle; Meehan, Judith; Mullaly, Rachel; O'Cathain, Niamh; et al.
Abstract: Aim: Pulmonary haemorrhage (PH) is an acute catastrophic event with low incidence yet high mortality among neonates. We aimed to systematically review the management of PH. Methods: A search was carried out of the PubMed, EMBASE and Cochrane databases according to the PRISMA guidelines. Data were extracted on study design and size, patient demographics, primary and adjunctive treatment methods, and treatment outcomes. Results: Sixteen studies with 385 newborn infants were included and were significantly heterogeneous regarding treatment methods. Primary treatments included surfactant, high‐frequency oscillatory ventilation (HFOV), epinephrine, coagulopathy management, intermittent positive pressure ventilation, cocaine and tolazoline. Adjunctive treatment methods included blood products, HFOV, increased positive end‐expiratory pressure, vitamin K, surfactant, adrenaline, vasopressors and inotropes. All five studies using surfactant as primary treatment were effective in improving oxygenation index measures and preventing recurrence of PH, and three studies found no association between surfactant and death or long‐term disability. Ventilatory support, epinephrine, management of coagulopathy and tolazoline were all found to be effective primary treatments for PH. Conclusion: There are several effective methods of managing PH in neonates. Further understanding of the aetiology of PH and ongoing research will allow future prevention and improvements in management of PH.